Evaluasi Pemanfaatan Ruang Kabupaten Lampung Selatan Tahun 2012-2017 - Zulqadri Ansar (Journal of Science and Applicative Technology, 2021)
Land use in South Lampung Regency continues to experience development, which is influenced by rapid population growth within five years after the planning year began in 2010. Various types of land-use changes that have occurred in South Lampung Regency indicate in the spatial changes of South Lampung Regency, which has been planned especially in the Regional Spatial Plan (RTRW) of South Lampung Regency for 2011-2031, one of which is the plantation area (belonging to PTPN VII) to become land for ITERA. There are preventive measures that can be made so that the spatial plan can still be following its development objectives. It is necessary to research by evaluating South Lampung Regency's spatial use based on its spatial plan, especially by RTRW. Based on the analysis, there is a deviation of land use in South Lampung Regency with 48.46%, which is divided into spatial structure plans and spatial pattern plans.